A Weight-based DV-HOP Improved Localization Algorithm for Wireless Sensor Networks - Liu, Dandan; Peng, S.; Lin, K. C.; Zhang, J. (International Journal of Online and Biomedical Engineering (iJOE), 2014)
DV-Hop is one of the range-free localization algorithmsusing hop-distance estimation. However, it suffersfrom a large localization deviation and low localization accuracy.This paper proposed a weight-based DV-HOP improvedalgorithm. It improves the traditional DV-HOP algorithmmainly in the following aspects. First, it increasesthe calculation accuracy of hop counts. Second, it correctsthe average hop distance calculated by the anchor node byusing least square method. Third, the un-located nodes calculatethe distance to other anchor nodes based on the linkstate with weights. The simulation results showed that theproposed algorithm significantly reduces the localizationdeviation, with a small increase in the node’s computationand communication cost. It is superior to the existing DVHOPalgorithm.